Trilateral Relationship: Ascaris, Microbiota, and Host Cells. Issue 3 (March 2021) - Midha, Ankur; Ebner, Friederike; Schlosser-Brandenburg, Josephine; Rausch, Sebastian; Hartmann, Susanne
Abstract : Ascariasis is a globally spread intestinal nematode infection of humans and a considerable concern in pig husbandry. Ascaris accomplishes a complex body migration from the intestine via the liver and lung before returning to the intestine. Tissue migration and the habitat shared with a complex microbial community pose the question of how the nematode interacts with microbes and host cells from various tissues. This review addresses the current knowledge of the trilateral relationship between Ascaris, its microbial environment, and host cells, and discusses novel approaches targeting these interactions to combat this widespread infection of livestock and man. Highlights: Recent studies are uncovering a complex interplay between gastrointestinal helminths, gut microbes, and the immune system. Parasitic helminth infections are associated with alterations to the intestinal microbiome and metabolome, and these interactions are thought to influence host susceptibility to infections with nematodes and bacterial pathogens. Technological advances make it possible to probe these interactions in considerable depth, and the large roundworm Ascaris presents a particularly interesting opportunity: Ascaris infections in pigs essentially mirror the human disease, and the pig is being rapidly developed as a human-relevant model for infectious diseases.